Synthesis, characterization and DNA binding activity of a potential DNA intercalator - Harun, Siti Norain; Razak, Yaakob; Ahmad, Haslina (Malaysian Analytical Sciences Society, 2016)
A novel complex, [Ru(dppz)2(p-MOPIP)]2+ (dppz = dipyrido-[3,2-a:20,30-c]phenazine, p-MOPIP = 2-(4-methoxyphenyl) imidazo[4,5-f][1,10]phenanthroline) has been synthesized and characterized by elemental analysis, 1H Nuclear Magnetic Resonance spectroscopy, mass spectrometry, Fourier Transform Infrared analysis, Ultra Violet visible and fluorescence spectroscopy. Herein, the complex was designed by adding p-MOPIP as an intercalating ligand and dppz as the ancillary ligand. The DNA binding properties of the complex with Calf Thymus DNA (CT-DNA) were investigated using spectroscopic methods. The UV-visible absorption band observed at 460 nm corresponded to the metal-to-ligand charge transfer (MLCT) while bands at 358 and 281 nm corresponded to intra-ligand (IL) π-π* transitions of the ligand scaffold in p-MOPIP and dppz. The intrinsic binding constant, Kb for this complex was 1.67 x 106 M-1 and this suggested that this complex, [Ru(dppz)2(p-MOPIP)]2+ bound to DNA via the intercalative mode. Interestingly, the interaction of this complex with CT-DNA also had a ‘molecular light switch’ effect.